Evaluation of health hazards associated with wastewater irrigation in Yola Adamawa State, Nigeria (International Journal of Irrigation and Water Management, 2014)
The study was conducted to assess the health risks from the use of wastewater for irrigation to ensure a sustainable and safer agricultural production. Samples of wastewater and lettuce wash-water were analyzed to determine the faecal coliform count and the presence of helminth eggs. Besides, the opinion of the public was seeked through the use of questionnaire. The data collected were analysed using some statistical analysis (ANOVA), correlation analysis and simple statistics. The result shows that there were significant differences (p ≥ 0.05) among the faecal coliform counts in the wastewater of the study area. However, in the case of the lettuce wash-water, there were no significant differences (P ≥ 0.05) among the values of the faecal coliform in the area except that of Bajabure which differed significantly from the rest. The result also shows that there was no correlation (r = - 0.15) between the faecal coliform in the wastewater and that in the lettuce wash-water. Helthminth eggs were found to be present in some of the wastewater and the lettuce wash-water of the study area.